Proceedings of the 2010 ACM Conference on Computer Supported Cooperative Work 2010
DOI: 10.1145/1718918.1718931
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting and focusing geographic volunteer work

Abstract: Open content communities such as wikis derive their value from the work done by users. However, a key challenge is to elicit work that is sufficient and focused where needed. We address this challenge in a geographic open content community, the Cyclopath bicycle route finding system. We devised two techniques to elicit and focus user work, one using familiarity to direct work opportunities and another visually highlighting them. We conducted a field experiment, finding that (a) the techniques succeeded in elic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…For example, Cyclopath is being successfully used to digitally map route information for bicyclists in Minneapolis. The system has been widely studied by the academic community, both in terms of its design and rationale [18], its effectiveness [20] and in terms of user's participation and behavioural analysis [19,15,16]. In [19], for example, the authors investigated the techniques and motivations that lead to an increased amount of volunteered geographic information in Cyclopath.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Cyclopath is being successfully used to digitally map route information for bicyclists in Minneapolis. The system has been widely studied by the academic community, both in terms of its design and rationale [18], its effectiveness [20] and in terms of user's participation and behavioural analysis [19,15,16]. In [19], for example, the authors investigated the techniques and motivations that lead to an increased amount of volunteered geographic information in Cyclopath.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The system has been widely studied by the academic community, both in terms of its design and rationale [18], its effectiveness [20] and in terms of user's participation and behavioural analysis [19,15,16]. In [19], for example, the authors investigated the techniques and motivations that lead to an increased amount of volunteered geographic information in Cyclopath. They found that visually highlighting contribution opportunities and asking users to work on an area that they are mostly familiar with, lead to better coverage.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The key passage in this email was: You will be presented with a area on the map. Read launched an experimental trial (the procedure as well as the code for conducting trials was adapted from [29]):…”
Section: Methodsmentioning
confidence: 99%
“…As of May 17, 2011, Cyclopath had 3,232 registered users and visits from 69,754 different IP addresses. Cyclopath has served as an excellent research platform for prior research on user behavior in social production communities, including studying efficient ways of eliciting contributions [29], user lifecycles [27] and specialization of contributions [26].…”
Section: Research Platformmentioning
confidence: 99%
See 1 more Smart Citation